Population's adherence to the Portuguese Health Examination Survey: the perspective of fieldwork teams - Gil, Ana Paula (2015)
The participation of fieldwork teams is key to successful surveys implementation. Thus, the Portuguese National Health Examination Survey (INSEF) is involving fieldwork teams in survey quality control processes. The aim of this presentation is to report a midterm evaluation's results of the internal quality control concerning participants' recruitment strategies and how these influence participation rate. A focus group discussion was carried out with fieldwork teams (nurses, laboratory technicians and administrative staff) and regional coordinators in the North, Center and Algarve regions. Each focus group had between 8 to 14 participants with an average age of 47 years and a long professional experience with an average of 22 years. A slideshow presentation fostered the discussion of the survey process: strengths and weaknesses of training, recruitment, informed consent, physical exam, blood collection, interview and logistical issues. It also explored the teams' perceptions of local cultural attitudes and the strategies used within the fieldwork. A thematic content analysis was performed. According to fieldwork teams, higher participation rates depend on: invitation letter signed by personal General Practitioner; free clinical analysis; pride in being selected in a scientific study; study conducted by experienced health professionals; data collection in local health center, schedule flexibility, invitation and confirmatory telephone calls. Also important: population's size, cultural factors and fieldwork teams' years of experience. In two focus groups, opinions on invitation letters' legibility differed between socio-professional categories: nurses and administrative staff. Participation rate depends on fieldwork teams' credibility and local community. The use of qualitative methods such as focus group is important to improve survey processes and these can also give valuable input on fieldwork teams' engagement and motivation.